Motivations of Chinese Tourists to Choose Malaysia as the prefer Tourist Destination - Yu, Jiyao (2014)
Tourism industry is now recognized as one of the important industry which is experiencing growth and able to survive in the midst of economic crisis. So many countries are currently vying each other to promote their respective tourism industries as one of the source country’s income, especially for Malaysian government where the tourism industry has emerged as the country’s second largest revenue earner after manufacturing. In 2013, there is about 97 million Chinese tourists went abroad, which is the biggest outbound market in the world an after 2012, Chinese travelers became the world’s biggest spenders, who can bring more than $1, 000 for the tourism destination. However, based on record of arrivals from China in recent years, the growth rate shows a downward trend. After incident of MH370, there are fewer Chinese tourists will choose the Malaysia as their tourism destination. Therefore, the objective of this research is to get a better understanding on what Chinese tourists’ motivation towards Malaysia as a tourism destination and how influence factors impacting on Chinese tourists to choose the tourism destination. The influencing factors that are implemented in this research are Novelty Seeking, Stress Busting/Fun, Achievement and Financial Incentives. Questionnaires are disseminated to 300 Chinese tourists who had a travel experience in Malaysia and several SPSS software has been used to analyze the results. The results show that overall factors have a positive influence toward choosing the Malaysia as the tourism destination. Further recommendations and discussions of the results for further research are also provided.